Religijność mieszkańców Śląska Cieszyńskiego w ujęciu statystycznym - Żebrok, Przemysław (Człowiek i Społeczeństwo, 2021)
In recent years Poland has been undergoing rapid socio-cultural changes. Along with these changes one can observe a systematic decline in the importance of religious life. This leads to reflection on the direction and depth of transformations, and consequently on the place of religion in the life of future generations. The study attempts to statistically present the religious situation of the inhabitants of Cieszyn Silesia. This is a very specific region mainly due to the diversity of confessions. Historical conditions, as well as the current religious structure make this subject difficult to study, but at the same time very interesting. For a more complete picture, the data from the beginning of the 20th century, as well as from the present day, were used.